THE MYTH OF THE BATTLE BETWEEN POSEIDON AND POLYBOTES: WAS THE INSPIRATION FROM A LATE HOLOCENE ROCK AVALANCHE AT ZINI, KOS ISLAND? - de Boer, Jelle Zeilinga; Pe-Piper, Georgia; PIPER, David J.W. (Bulletin of the Geological Society of Greece, 2022)
Scenes of the legendary battle between Poseidon and the giant Polybotes, which occurred on the Greek island of Kos, are depicted on dozens of surviving ceramic objects. Poseidon is shown killing his opponent with his trident, while carrying a huge rock that he had ripped off the island of Kos to bury Polybotes. The legend is interpreted to represent a strong earthquake that caused a large coastal rock fall or rock avalanche. The oldest ceramics representing this disaster date from ca. 540 BCE. The disaster is interpreted to date from this time and was a major event that reverberated throughout the Greek world, triggering the imagination of its artists for several generations. Legend and ancient literary sources suggest that the event took place in southeastern Kos, near the then capital city of Astypalaia, located NW of Zini mountain. Geological studies show a large, relatively recent, rock avalanche on the steep coast on the SE side of Zini mountain. Possible tsunami sand deposits with reworked marsh foraminifera are found 7 m above sea level on NE Zini, only 1 km from the archeological site of the old city of Astypalaia and large boulders are stranded on the opposite rocky coastline up to 6 m above sea level. Noise and dust from a rock avalanche would have been terrifying for the inhabitants of Astypalaia and any tsunami would have overwashed the port at Kamari. In the absence of suitable geological dating methods, ceramics provide the best chronology for the event.